Highly selective and sensitive detection of glutathione using mesoporous silica nanoparticles capped with disulfide-containing oligo(ethylene glycol) chains. Issue 4 (8th December 2014) - El Sayed, Sameh; Giménez, Cristina; Aznar, Elena; Martínez-Máñez, Ramón; Sancenón, Félix; Licchelli, Maurizio
Abstract : Mesoporous silica nanoparticles loaded with safranin O and capped with disulfide-containing oligo(ethylene glycol) chains were used for the selective and sensitive fluorimetric detection of GSH. Abstract : Mesoporous silica nanoparticles loaded with safranin O and capped with disulfide-containing oligo(ethylene glycol) chains were used for the selective and sensitive fluorimetric detection of glutathione.